214PTargeting epithelial-mesenchymal transition (EMT), novel strategy to delay resistance or re-sensitize renal cancer to Sunitinib. (24th November 2019) - Sharma, R; Kadife, E; Kannourakis, G; Ahmed, N; Prithviraj, P
Abstract: Background: Epithelial-Mesenchymal Transition (EMT) is a dynamic process hypothesized to occur in carcinoma during invasion and metastasis. Tyrosine Kinase Inhibitor Sunitinib stands as the main first-line treatment in metastatic renal clear cell carcinoma (mRCC). Activation of IGF and TGFβpathways are known to be associated with the acquisition of EMT and chemoresistance in cancer cells. Downregulation of EMT regulators is a promising therapeutic strategy to overcome resistance or resensitize RCC to Sunitinib therapy. Furthermore, indirect and specific inhibition of IGF axis by inhibition of PAPP-A, which regulates IGF signaling, represents a novel approach in mRCC treatment. Methods: RCC tumor tissues, primary and metastatic RCC cell lines (parental and Sunitinib resistant) were examined for EMT proteins (Ecad & Ncad), EMT regulators, TGFβ and IGF/PAPP-A axis by qRT-PCR and western blot. Analysis of TCGA transcriptome profiling dataset was performed. Results: Higher expression of N cadherin and low expression of E cadherin indicating mesenchymal signature was noted in RCC patient tumors associated with significantly upregulated expression of known EMT inducers; TGFβ and IGF1R as compared to non-tumor adjacent kidney tissues. Expression of IGF1 axis components, EMT markers and TGFβ was confirmed via qRT-PCR in primary and metastatic RCC cell lines. Sunitinib-induced EMT was confirmed by upregulation of N cad and downregulation of Ecad in 786-O RCC cell line. Analysis of TCGA dataset revealed that IGF1R expression (n = 792, HR 1.45, p = 0.01) and TGFβ expression (n = 792, HR 2.14, p < 0.01) resulted in worse overall survival in mRCC patients, a non-significant trend towards worse survival was noted with PAPP-A expression (n = 792, HR 1.27, p = 0.1). Conclusions: Our data suggest that EMT may play a role in RCC progression and may be a mechanism of drug resistance to Sunitinib. TGFβ and IGF pathways are dysregulated in RCC, therefore direct or indirect targeting of these pathways may prove to be a novel strategy to delay resistance to Sunitinib or resensitize RCC to VEGF inhibitor therapy. Legal entity responsible for the study: Fiona Elsey Cancer Research Institute. Funding: Fiona Elsey Cancer Research Institute. Disclosure: All authors have declared no conflicts of interest.